THE CONCEPT IN LINGUISTICS: ITS NATURE AND ROLE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In modern linguistics, the concept of "concept" is one of the central terms that reveal the connection between language and thinking. A person expresses his worldview, feelings and experiences in language. Therefore, language is studied not only as a means of communication, but also as a phenomenon that expresses culture, values and mentality. In linguistics, the concept of concept is at the heart of this process, because it is reflected through words, but contains a meaning that is broader than the word itself.